Concentrations of trace elements and KRAS mutations in pancreatic ductal adenocarcinoma. (23rd May 2019) - Gómez‐Tomás, Álvaro; Pumarega, José; Alguacil, Juan; Amaral, André F. S.; Malats, Núria; Pallarès, Natàlia; Gasull, Magda; Porta, Miquel; ,
Abstract : Trace elements are a possible risk factor for pancreatic ductal adenocarcinoma (PDAC). However, their role in the occurrence and persistence of KRAS mutations remains unstudied. There appear to be no studies analyzing biomarkers of trace elements and KRAS mutations in any human cancer. We aimed to determine whether patients with KRAS mutated and nonmutated tumors exhibit differences in concentrations of trace elements. Incident cases of PDAC were prospectively identified in five hospitals in Spain. KRAS mutational status was determined through polymerase chain reaction from tumor tissue. Concentrations of 12 trace elements were determined in toenail samples by inductively coupled plasma mass spectrometry. Concentrations of trace elements were compared in 78 PDAC cases and 416 hospital‐based controls (case–control analyses), and between 17 KRAS wild‐type tumors and 61 KRAS mutated tumors (case–case analyses). Higher levels of iron, arsenic, and vanadium were associated with a statistically nonsignificant increased risk of a KRAS wild‐type PDAC (OR for higher tertile of arsenic = 3.37, 95% CI 0.98–11.57). Lower levels of nickel and manganese were associated with a statistically significant higher risk of a KRAS mutated PDAC (OR for manganese = 0.34, 95% CI 0.14–0.80). Higher levels of selenium appeared protective for both mutated and KRAS wild‐type PDAC. Higher levels of cadmium and lead were clear risk factors for both KRAS mutated and wild‐type cases. This is the first study analyzing biomarkers of trace elements and KRAS mutations in any human cancer. Concentrations of trace elements differed markedly between PDAC cases with and without mutations in codon 12 of the KRAS oncogene, thus suggesting a role for trace elements in pancreatic and perhaps other cancers with such mutations. Environ. Mol. Mutagen., 60:693–703, 2019. © 2019 Wiley Periodicals, Inc.